Inseminations at estrus induced by the presynch protocol before timed artification insemination - Phatak, A.P.; Stevenson, Jeffrey S. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
A controlled field study examined conception rates after two timed-AI (TAI) breeding protocols conducted on two commercial dairy farms. Estrous cycles in postpartum lactating cows were presynchronized with two injections of PGF2" given 14 days apart (Presynch) and then, after 12 days, the standard Ovsynch protocol (injection of GnRH 7 days before and 48 h after an injection of PGF2", with one TAI at 12 to 16 hours after the second GnRH injection) or Heatsynch protocol (injection of GnRH 7 days before an injection of PGF2", followed 24 h later by 1 mg of estradiol cypionate (ECP) and one TAI 48 hours after ECP) was applied. Experimental design allowed for AI to occur any time after the second Presynch injection and during the designed breeding week when estrus was detected. Of the 1,846 first services performed, only 1,503 (rate of compliance = 81.4%) were performed according to protocol. Numbers of cows inseminated, logistic-regression-adjusted conception rates, and days in milk (DIM) were for inseminations made: 1) during 14 days after first Presynch injection (n = 145; 22.6%; 54 ± 0.4 DIM); 2) during 12 days after second Presynch injection (n = 727; 33%; 59 ± 0.2 DIM); 3) during 7 days after the first GnRH injection of Ovsynch or Heatsynch (n = 96; 32.1%; 74 ± 0.5 DIM); 4) after estrus as part of Heatsynch (n = 212; 44.6%; 76 ± 0.3 DIM); 5) after TAI as part of Heatsynch (n = 154; 21.1%; 76 ± 0.4 DIM); 6) after estrus as part of Ovsynch (n = 43; 48.7%; 77 ± 0.7 DIM); and 7) after TAI as part of Ovsynch (n = 271; 24.4%; 77 ± 0.3 DIM). Conception rates when AI occurred after one Presynch injection were less than when AI occurred after two Presynch injections. Conception rates for those inseminated after either Presynch injection did not differ from those inseminated after combined Heatsynch + Ovsynch. Cows in the Ovsynch and Heatsynch protocols inseminated after estrus during the breeding week had greater conceptions rates than those receiving the TAI, but overall conception rates did not differ between protocols. Among cows inseminated after detected estrus, conception was greater for cows in the Heatsynch + Ovsynch protocol (77 ± 0.4 DIM) than for those inseminated after either Presynch injection (54 ± 0.4 or 59 ± 0.2 DIM). We concluded that conception rates after Heatsynch and Ovsynch were similar under these experimental conditions, and that delaying first AI improved fertility for cows inseminated after detected estrus.
Keywords: Dairy; Calving difficulty; Compliance; Conception; Synchronized estrus